The Students’ Motivation in Writing through Mind Mapping at Tomakaka University of Mamuju - Nurul Hasanah; Syahban Mada Ali (Universitas Muhammadiyah Enrekang, 2020)
The aim of this research is to find out whether the use of mind mapping can motivate the students in writing. The method was used is mix method (Quantitative and Qualitative). The subject of this research was the second semester students of Tomakaka University of Mamuju. The data was collected and analyzed through scoring scale which includes the content, organization, vocabulary, language use and mechanics by using Jacob’s scoring rubric. Then, to find out the students are motivated through the method applied or not, it was used questionnaire and interview. The questionnaire wasanalyzed by the Likert scale, it is divided into strongly motivated, motivated, fairly motivated, unmotivated, and strongly unmotivated.Then, interview are used to confirm the students answers in the questionnaire. The result of this research is the second semester students of TomakakaUniversity of Mamuju are motivated in writing through Mind Mapping method. It can be shown from the data of writing test, questionnaire and interview. The result of the treatment given showed a trend of increasing students’ writing score. And also, students gave positive responses to the questionnaire distributed where most students answered that Mind Mapping method was very useful in increasing their writing motivation.